Analysis of the Work Motives of Wonocolo Traditional Oil Miners - Joko Hadi Susilo; Hartiningsih Astuti; Sahra Dwi Irma Rosida; Dimas Surya Atmaja; Jennifer Kasanda Sesabo (Universitas Negeri Semarang, 2026)
This study aims to analyze the influence of physical environmental factors (geosite) and cultural environmental factors (culturesite) on the work motivation of traditional oil miners in Wonocolo Village, Bojonegoro Regency in 2025. This research is motivated by the unique characteristics of Wonocolo traditional oil mining which is still managed traditionally and is a historical legacy from the Dutch era. In addition, the issue of developing geosites, geoparks, and sustainable economic transformation is currently an important concern in local resource-based regional development. The research subjects were traditional oil miners who were still actively working and directly involved in the production process. The study used a descriptive quantitative approach with data collection techniques through closed questionnaires using a Likert scale. The research sample was determined using the snowball sampling technique considering the informal characteristics of workers. Data analysis was carried out using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of WarpPLS software. The results of the study show that geosites have a negative and significant effect on work motivation, which indicates that increasing public awareness of the geological value and potential for regional development encourages reduced dependence on mining activities as the main livelihood. However, this condition does not necessarily make people leave their jobs as miners due to limited alternative jobs and household economic considerations. Meanwhile, culturesite does not have a significant effect on work motivation, which shows that cultural values and mining traditions have not become a dominant factor in people's decisions to work as miners. These findings indicate that economic motives are still the primary consideration for people in maintaining employment in the traditional mining sector. This research contributes to the development of geosite and culturesite-based development economic studies, and has important implications for the formulation of Wonocolo area management policies towards a more sustainable local economic transformation through the development of geotourism and alternative economies based on local potential.